Understanding the influence of socioeconomic status on children physical disciplinary practices in Bangladeshi households - Mahnaz Ibrahim; Md Hridoy Patwary (PLoS ONE, 2025)
Background Despite progress in reducing violence against children, physical disciplinary practices remain prevalent in many parts of the world, including Bangladesh. Understanding the sociodemographic factors contributing to these practices is crucial for developing effective interventions to protect children from violence. This study aims to estimate the prevalence and impact of household economic status on the physical disciplinary practices experienced by children under five years old in various sociodemographic contexts. Methods Data from the Bangladesh Multiple Indicator Cluster Survey (MICS) 2019 was used to explore physical disciplinary practices against children under five, focusing on factors such as household wealth, region, type of residence, child’s gender, and mother’s education level. Logistic regression analysis was employed to examine the adjusted association between sociodemographic factors and physical disciplinary practices. Findings The study found that 64.88% of children under five experienced physical disciplinary practices at home. The odds of being subjected to PDP were higher for children from lower wealth index categories (poorest, poorer, middle, richer) compared to those in the richest category, with AORs ranging from 1.21 to 1.35 and all p-values <0.01. Urban residence was associated with increased odds of being physically punished (AOR: 1.09, 95% CI: 1.01–1.20). Boys had higher odds of being physically punished compared to girls (AOR: 1.15, 95% CI: 1.07–1.23). The odds of being physically punished were greater for children of less-educated mothers. Furthermore, mothers who believed that physical punishment was necessary for child-rearing had higher odds of using such practices (AOR: 2.10, 95% CI: 1.94–2.27). Conclusion Socioeconomic factors, especially household wealth, significantly influence the risk of experiencing physical disciplinary practices among children. The findings emphasize the need for targeted interventions to protect vulnerable children, particularly in urban and impoverished settings.